Autonomy or Submission? The Position of Women in the Tradition of Londho iha (Elopement) in Bima, West Nusa Tenggara, Indonesia - Iva Yulianti Umdatul Izzah; Tiara Senjaya; Ridha Amaliyah (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
The practice of elopement among the Bima people is closely tied to traditional dynamics, local norms, legal frameworks, and religion. This study examines the role of women in elopement and whether it is a form of autonomy or submission. Using qualitative research methods, the study focuses on elopement (londho iha) in Samili Village, located in Woha District, Bima Regency, West Nusa Tenggara. The findings reveal that women occupy a nuanced position in londho iha, one that is both autonomous and submissive. On the one hand, this tradition can be interpreted as a way for women to express their autonomy in choosing a life partner. On the other hand, it functions as a social mechanism that subjects women to customary and social pressures. Women in the londho iha tradition are complex subjects. They have the agency to make decisions, but these decisions are often constrained by patriarchal norms that govern their lives. Londho iha is not merely a patriarchal tradition, but also a space in which Bima women strive to exercise their agency within the constraints of a complex social system. Women's agency in londho iha is ambivalent. It can liberate them, but it can also trap them within patriarchal structures. Thus, this practice should be understood as a dynamic interplay of power, culture, and the acting subject rather than as a manifestation of total domination or absolute freedom.